2001
DOI: 10.4102/jsava.v72i4.651
|View full text |Cite
|
Sign up to set email alerts
|

Use of ethnoveterinary medicinal plants in cattle by Setswana-speaking people in the Madikwe area of the North West Province of South Africa

Abstract: Rapid Rural Appraisal (RRA) methods were employed to document the use of ethnoveterinary medicinal plants in cattle by Setswana-speaking people in the Madikwe area of the North West Province of South Africa. The study indicated that Setswana-speaking people in the North West Province have a rich heritage of ethnoveterinary knowledge, which includes all aspects of ethnoveterinary medicinal plant use. Information was gathered from informants through individual interviews, group interviews, guided field walks and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(81 citation statements)
references
References 23 publications
5
76
0
Order By: Relevance
“…The results as assessed in the present study are in agreement with the observations of (Haile and Delenasaw 2007). The use of toxic plants in ethno veterinary preparations as was observed in the study has also been reported by Van der Merwe et al (2001), Muhammad et al (2006), Kumar and Sharma (2012) and Naik et al (2012) from different parts of the world.…”
Section: Resultssupporting
confidence: 77%
“…The results as assessed in the present study are in agreement with the observations of (Haile and Delenasaw 2007). The use of toxic plants in ethno veterinary preparations as was observed in the study has also been reported by Van der Merwe et al (2001), Muhammad et al (2006), Kumar and Sharma (2012) and Naik et al (2012) from different parts of the world.…”
Section: Resultssupporting
confidence: 77%
“…If the plant is crushed and left overnight in water, the resultant mucilage from the leaves becomes a useful substitute for soap and shampoo (Van Wyk and Gericke, 2000). In terms of medicinal purposes, DE can be used for antibacterial (Luseba et al, 2007) and ethnoveterinary medicines (Van Der Merwe et al, 2001). Parts of the plant have been used to treat diseases in the rural areas of the Vhembe District, South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…In animals, the most commonly treated disorders comprise diarrhea, and general gastrointestinal problems, internal parasites, eye inflammation, retained placenta, heartwater, coughing, redwater and tick infestation [33]. It is critical when evaluating herbal remedies used in animal health care to bear in mind that ethnoveterinary medicine as a whole includes diagnostic procedures, animal husbandry practices, surgical methods and traditional veterinary theory in addition to the use of ethnoveterinary plants to prevent and control disease [33,34].…”
Section: Traditional Ethnoveterinary Medicinementioning
confidence: 99%
“…It is critical when evaluating herbal remedies used in animal health care to bear in mind that ethnoveterinary medicine as a whole includes diagnostic procedures, animal husbandry practices, surgical methods and traditional veterinary theory in addition to the use of ethnoveterinary plants to prevent and control disease [33,34].…”
Section: Traditional Ethnoveterinary Medicinementioning
confidence: 99%